Changing epidemiology of AA amyloidosis: clinical observations over 25 years at a single national referral centre. (3rd July 2017) - Lane, Thirusha; Pinney, Jennifer H.; Gilbertson, Janet A.; Hutt, David F.; Rowczenio, Dorota M.; Mahmood, Shameem; Sachchithanantham, Sajitha; Fontana, Marianna; Youngstein, Taryn; Quarta, Candida C.; Wechalekar, Ashutosh D.; Gillmore, Julian D.; et al.
Abstract: Objective: Systemic AA amyloidosis is a serious complication of chronic inflammation; however, there are relatively few published data on its incidence. We investigated the changing epidemiology of AA amyloidosis over a 25-year period at a single national referral centre. Methods: We conducted a retrospective study of all patients diagnosed with AA amyloidosis who had attended the centre between 1990 and 2014 inclusive. Six hundred and twenty-five patients were studied in three cohorts: C1: 1990–1997; C2: 1998–2006; C3: 2007–2014. Results: Mean age at presentation increased from 46 in C1 to 56 in C3 ( p < .0001). The proportion of South Asian patients increased from 4% in C1 to 17% in C3 ( p = .0006). Comparison of underlying diseases between C1 and C3 revealed a reduction in patients with juvenile idiopathic arthritis from 25% to 2% ( p < .0001), but an increase in patients with chronic infection due to intravenous recreational drug use from 1% to 13% ( p < .0001), and uncharacterized inflammatory disorders from 10% to 27% ( p <.0001). More patients were in end-stage renal failure at presentation in C3 (29%) than C1 (15%) ( p = .0028). Median age at death was later in C3 (62 years) than C1 (54 years) ( p = .0012). Conclusion: These data suggest both falling incidence and better outcome in AA amyloidosis over a quarter of a century, reflecting advances in therapeutics and overall management of complex chronic disease in an ageing population. AA amyloidosis of uncertain aetiology presents an emerging major problem. Newer techniques such as next-generation sequencing may aid diagnosis and effective treatment, thereby improving overall survival.